2020
DOI: 10.1097/cce.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-Specific Enolase Levels in Adults Under Venoarterial Extracorporeal Membrane Oxygenation

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
(31 reference statements)
0
11
1
Order By: Relevance
“…Notably, although the results of our analysis showed no significant difference between the SAE and NE groups after 24 h, it does not exclude the diagnostic efficacy of NSE for SAE over 24 h. This may be related to the small sample size of studies we included in the over-24 h analysis and the large heterogeneity (up to 99%) among the studies. In addition to this, we found from studies of other diseases that NSE after 72 h was associated with mortality and poor functional prognosis in patients under venoarterial extracorporeal membrane oxygenation (38) as well as in cardiac arrest (39). Therefore, more multicenter large-sample studies are still needed to explore the prognostic role of NSE for prolonged periods of time (>24 h).…”
Section: Discussionmentioning
confidence: 94%
“…Notably, although the results of our analysis showed no significant difference between the SAE and NE groups after 24 h, it does not exclude the diagnostic efficacy of NSE for SAE over 24 h. This may be related to the small sample size of studies we included in the over-24 h analysis and the large heterogeneity (up to 99%) among the studies. In addition to this, we found from studies of other diseases that NSE after 72 h was associated with mortality and poor functional prognosis in patients under venoarterial extracorporeal membrane oxygenation (38) as well as in cardiac arrest (39). Therefore, more multicenter large-sample studies are still needed to explore the prognostic role of NSE for prolonged periods of time (>24 h).…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies suggested an association between NSE levels and outcomes in cardiac arrest patients ( 35 ), stroke patients ( 36 ), VA-ECMO patients ( 16 ), and sepsis-associated encephalopathy ( 37 ). The absence of a significant association between NSE levels and sepsis in our study may be confounded by several factors, including cerebral hypoxia before ECMO cannulation, and hemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Different non-invasive tools may help clinicians identify brain injury and assist with prognostication during VA-ECMO support ( 14 ). These tools include a clinical evaluation using automated pupillometry ( 15 ), serum neuronal/glial injury biomarkers ( 16 ), spot or continuous EEG ( 17 , 18 ), and neuroimaging in selected cases ( 19 ).…”
mentioning
confidence: 99%
“…It is well known that the NSE enzyme is also present in the cell membrane of erythrocytes and platelets and increases in blood with hemolysis. [13,14] We considered that the differences in cross-clamp (CC) and CPB times among the groups could affect the NSE enzyme level. However, when we examined the CC and CPB times of our patients, there was no significant difference among the groups.…”
Section: Discussionmentioning
confidence: 99%